I need help. Thank you.
![I need help Thank you class=](https://us-static.z-dn.net/files/d2a/6912e9ef40521aadc7b942982bdb7c8b.png)
Answer:
v=b (the answer is option b.)
Step-by-step explanation:
3b=6v−3b
Rewrite the equation as 6v−3b=3b.
6v−3b=3b
Move all terms not containing v to the right side of the equation.
Add 3b to both sides of the equation.
6v=3b+3b
Add 3b and 3b.
6v=6b
Divide each term by 6 and simplify.
Divide each term in 6v=6b by 6.
6v/6=6b/6
Cancel the common factor of 6.
v=6b/6
Cancel the common factor of 6.
v=b
Hope this helps! Plz mark as brainliest! :)